The Competitive Earning Incentive for Sons: Evidence from Migration in China - Wenchao Li; Junjian Yi (Institute for the Study of Labor (IZA), 2015)
This paper first finds a clear pattern of child gender difference in family migration in China. Specifically, our estimates show that on average, the first child being a son increases the father's migration probability by 25.2 percent. We hypothesize that the family's competitive earning incentive for sons drives this child gender effect on family migration: parents migrate to earn more money in an attempt to improve their sons' relative standing in response to the ever-rising pressure in China's marriage market. This competitive-earning-incentive hypothesis is then supported by additional empirical evidence. We further find that, facing heavier financial pressure from the marriage market, parents spend less on their sons' education and more on marriage and buying houses and durable goods. This gender difference in resource allocation, together with the absentee-father problem resulting from paternal migration, may unexpectedly adversely affect boys' long-run human capital development in China.
Keywords: J11; J13; O15; 330; competitive earning incentive; sex ratio; migration